Reshaping the graduate education of scientists and engineers (National Academy Press, 1995)
Presents the electronic book "Reshaping the Graduate Education of Scientists and Engineers" by the National Academy of Sciences and published by National Academy Press. Notes that graduate work in science and engineering must coincide with modern industry standards and skills requirements.
This project was supported by the National Science Foundation, the U.S. Department of Energy, and the Kellogg Endowment Fund of the National Academy of Sciences and the Institute of Medicine.
Keywords: Science -- Study and teaching -- United States.; Engineering -- Study and teaching -- United States.; Science -- education; Engineering -- education; United States; Ingénierie -- Étude et enseignement -- États-Unis.; SCIENCE -- Study & Teaching.; Engineering -- Study and teaching; Science -- Study and teaching